Hello all; a homework question that is confusing me:
1) Find the Maclaurin Series for this function: f[x] = e^x + 2e^-x. Can I just make this
Sum(0 to Infinity) of x^n/(n!) + 2Sum(0 to Infinity) of (-x)^n/(n!) ??
Hello all; a homework question that is confusing me:
1) Find the Maclaurin Series for this function: f[x] = e^x + 2e^-x. Can I just make this
Sum(0 to Infinity) of x^n/(n!) + 2Sum(0 to Infinity) of (-x)^n/(n!) ??
Yes, but you can combine some terms:
$\displaystyle \sum_{n=0}^{\infty}\frac{x^n}{n!}+2\sum_{n=0}^{\in fty}\frac{(-x)^n}{n!} = 1+2+x-2x+\frac{x^2}{2}+2\frac{x^2}{2}+\frac{x^3}{6}-2\frac{x^3}{6}+...= 3-x+\frac{3x^2}{2}-\frac{x^3}{6}+...$
If $\displaystyle n$ is even, the coefficient is $\displaystyle 3$; if $\displaystyle n$ is odd, $\displaystyle -1$; it can therefore be represented as $\displaystyle 1+2(-1)^n$
So the series is $\displaystyle \sum_{n=0}^{\infty}\frac{(1+2(-1)^n)x^n}{n!}$